Sintesis dan Karakterisasi Biodiesel Berbasis Minyak Jelantah Mengunakan Metode Rute Non-Alcohol - Humaira, Nur; Zulkifli, Zulkifli; Saifuddin, Saifuddin (Jurnal Teknologi, 2024)
Biodiesel as an alternative fuel to replace diesel has a very important function for the availability of long-term energy supply. The purpose of this study was to determine the effect of reactant ratios and the use of catalysts on the characteristics of biodiesel from used cooking oil using the non-alcoholic route. This research was conducted using the non-alcoholic route method by varying the reactant ratio (1:2, 1:3, 1:4, 1:5, 1:6) mol and varying the KOH catalyst (0.2; 0.3; 0.4 ; 0.5; 0.6)% of the mass of used cooking oil. The results showed that the reactant ratio of 1:6 and 0.6% catalyst was the best result by producing 0.16% FFA, viscosity of 3.5 cSt, density of 860 kg/m3, heating value of 8916.826 Kcal/g, cetane number of 76.8. From the results of the analysis above, it shows that the biodiesel produced is included in the SNI 04-7182: 2015 standard.